Problematik Definisi Harta Pailit untuk Mencapai Kepastian Hukum dalam Pelaksanaan Kepailitan dan PKPU - Adriel Michael Tirayo; Yoefanca Halim (Jurnal Ilmiah Penegakan Hukum, 2019)
A legal product is expected to realize 3 legal purposes, which is Justice, Expediency and Legal Certainty. The definition of bankrupt assets is not mentioned implicitly in the Bankruptcy Law, that can lead to multiple interpretations. In practice, it happened in the court judgement Number 33/Pailit/2009/PN.Niaga.Jkt.Pst for the bankruptcy of PT. Tripanca Group, due to the absence of clear provisions relationg to bankruptcy assets. In this case, the problem to be answered is how is the implementation of bankrupt assets definitions in the court judgement Number 33/Pailit/2009/PN.Niaga.Jkt.Pst and the efforts that can be made related to the implementation of bankrupt assets definitions. This research used normative juridical method through literature study, then the data has been analized qualitatively and conclusions are drawn inductively. The results showed that the definition of "bankruptcy assets" in practice led to multiple interpretations as contained in the court judgement Number 33/Pailit/2009/PN.Niaga.Jkt.Pst, where the judge also included assets that did not belong to the debtor (third party collateral) into assets bankruptcy as a guarantee of repayment of debt. Therefore, efforts that can be made by the government are to revise the Bankruptcy Law, specifically related to the definition of Bankruptcy Assets to provide Legal Certainty and to disseminate information to legal entities, non-legal entities, and the public so as to gain understanding and knowledge related to Bankruptcy and PKPU in particular about bankruptcy assets.